Analyzing Aceh Cultural Heritage: Mathematical Tools and Language Use - Abidin, Zainal; Usman, Jarjani (SCAD Independent, 2021)
Acehnese people have many culturallyunique mathematical treasures, such as for measuring size and volume. Some of which are different from the ones used in other parts of Indonesia and some have been rarely used and even unknown by today’s generation. However, research on the measuring scales in Aceh is scant. This study was carried out to understand the Acehnese people’s prevailing measuring scales used. These scales are ethnomathematics parts of the Aceh culture. The research was conducted in six districts. Snowball sampling was employed through which people who are knowledgeable on Aceh culture were selected for interview. It shows that the volume scaling units of ethnomathematics in the culture of Aceh society are kay, aree, naleh, gateng, gunca, and kuyan. 1 kuyan = 10 gunca; 1 gunca = 10 naleh; 1 naleh = 16 aree; 1 aree = 4 kay. The size and volume of the kay, aree, naleh, gateng scales vary in each district.Moreover, the language used for scales and meanings slightly varies, such as naleh that is used for measuring volume or size only in some districts of Aceh and for both volume and size in other parts of the province.